Comparison of perinatal outcomes between controlled‐release dinoprostone vaginal delivery system (PROPESS) and metreurynter for cervical ripening in labor induction: A retrospective single‐center study in Japan. Issue 12 (20th September 2021) - Yamaguchi, Mizuki; Takakura, Sho; Enomoto, Naosuke; Teishikata, Yasuhiro; Kitamura, Asa; Maki, Shintaro; Tanaka, Kayo; Maezawa, Tadashi; Tanaka, Hiroaki; Ikeda, Tomoaki
Abstract: Aim: This study aimed to compare the efficacy and safety of a controlled‐release dinoprostone vaginal delivery system (PROPESS) and a metreurynter for labor induction. Methods: This retrospective case‐controlled study included 117 pregnant women (51 and 66 in the PROPESS and metreurynter groups, respectively) who required labor induction after >37 weeks' gestation at Mie University Hospital between January 2018 and September 2020. The primary outcome was the success rate of vaginal delivery. The secondary outcomes were changes in the Bishop score from the first insertion of PROPESS or the metreurynter to removal, uterine hyperstimulation and non‐reassuring fetal status during the first insertion, proportion of pregnant women who needed pre‐delivery oxytocin after removal, time to vaginal delivery after the first insertion, proportion of pregnant women who delivered vaginally within 12 or 24 h after the first insertion, and neonatal outcomes. Results: The proportion of pregnant women, especially primiparas, who delivered vaginally was significantly higher in the PROPESS group (26/34 [76.5%]) than in the metreurynter group (25/52 [48.1%]; p = 0.01). Moreover, among multiparas in the PROPESS group who delivered vaginally, nine (56.3%) out of 16 women delivered vaginally within 3 h of labor onset. Conclusions: PROPESS for cervical ripening may reduce the risk of undergoing cesarean section in pregnant women requiring labor induction, especially primiparas. It is important to consider the possibility of precipitate labor when using the PROPESS in multiparas.